Iraqi Communist Political Party Role in Hendren Battle and It’s Conclusions: Historical and Political Research - Rafiq Rahman Mam Khul; Ismail Muhammed Safah (QALAAI ZANIST SCIENTIFIC JOURNAL, 2023)
The Iraqi Communist Party, as an Iraqi party, has dozens of political and military cadres and organizations in Kurdistan and has played a major and influential role in the Battle of Hendren. As a result of this battle, a number of his cadres were killed and wounded. In order to demonstrate the role of the Communist Party in this battle, we conducted this research based on a number of sources and documents and interviews with contemporaries of the event and those who participated in it. This research plan was divided into three axes as follows: The first axis: the government's plan and map to capture the mountains of Hendren and Zozk. The second axis: the Iraqi army's attack on Hendren and how defended by Peshmerga. The Three axis: The military and political consequences of the Battle of Handren.